Manajemen Ekstrakurikuler Robotik dalam Mengembangkan Kreativitas Siswa di Era Social Society 5.0 - Fitriani, Latifa; Sutiah, Sutiah; Susilawati, Samsul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Extracurricular management supports the optimization of national education goals. The urgency of extracurricular management, apart from streamlining talent interest training, also plays a role in realizing educational goals, namely developing student creativity. Moreover, Indonesia's creativity index (GCI) is still low. So the management of robotic extracurriculars has relevance in welcoming the era of society 5.0, namely creating creative human resources. The purpose of this study was to analyze the planning, implementation, and evaluation of robotic extracurricular activities in developing the creativity of students in the 5.0 social era at SDIT Ahmad Yani Malang. Retrieval of data using interview techniques, observation, and documentation study Data analysis involves condensing data, presenting data, and verifying data. Checking the validity of the data with a credibility test, transferability test, dependability test, and confirmability test. The research conducted at SDIT Ahmad Yani Malang used a qualitative research approach with a case study type of research. The results of the research conducted show that (1) the planning of robotic extracurricular activities to develop the creativity of students in the 5.0 social era at SDIT Ahmad Yani Malang has been running effectively. This is marked by the preparations that have been made in such a way as to develop creativity through an early semester meeting and MOU cooperation with robotics. (2) The implementation of robotic extracurricular activities has been running effectively with the use of PjBL, STEM, demonstrations, and fun learning strategies. (3) The evaluation of robotic extracurricular activities also runs effectively with ongoing monitoring. Besides that, checking the effectiveness of robotic extracurricular management uses the 5M elements (people, methods, materials, machines, and money). While the output of student creativity is shown from the cognitive, psychomotor, and affective domains.